Safety Evaluation of Artocarpus altilis as Pharmaceutical Agent in Wistar Rats - Sudha Sairam; Asna Urooj (Journal of Toxicology)
This study was designed to elucidate the acute toxicity of Artocarpus altilis leaf and bark extracts. In acute toxicity study, no mortality or any toxic reaction was recorded in any group after 14 days of administering the extracts (2000 mg Kg−1 BW). The extracts (ALA, ABA, ALM, and ABM) did not cause any behavioural or physical changes in experimental rats. There was no significant (P≤0.05) difference in the biochemical parameters analysed between the groups. Slight elevation in activities of AST and ALT in extract treated groups was observed, but this did not exert any deleterious effect on the normal metabolism which was supported by the histopathology of liver. Histopathological studies showed no remarkable changes after 14 days of oral administration of ALA, ABA, ALM, and ABM extracts. The study contributes to establishing the nontoxic quality parameters of Artocarpus altilis leaf and bark parts and the results suggest the safety of the extracts in therapeutic uses.